Typomorphology: A Methodological Approach to Context Analysis in Architectural Design Education - Saylan, Seda; Gurer, Tan Kamil (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2024)
The study aims to demonstrate the importance of typomorphological knowledge as a method of contextual analysis in architectural design education. The Architectural Design Studio is a place for students to experience design tools, methods, and practice, and focuses on developing the ability to design and teach. Design, with its phases of analysis, synthesis, and evaluation phases, is a dynamic process that consists of adapting and transforming the information obtained from past experiences and making it suitable for the creation of new designs. The analysis phase is one of the most crucial stages in the architectural design process, as it involves the study of the context. The context typically includes tangible data such as topography, the built environment, functional relationships, the history of the area, and its current significance. The typomorphological approach is a method for studying context and is crucial to introduce into design education. The study intends to reveal the contribution of supporting imaginative education with theoretical knowledge to the design process and how typomorphological knowledge can be taught, in architectural design education. The paper analyzes the significance and role of context in architectural design education and process, provides knowledge on typomorphological approaches, and explores through examples the contributions of researchers using these approaches to design education in this field and how they produce solutions. The conclusion discusses the concepts, issues, and analytical techniques addressed by four different researchers in their architectural/urban design courses integrating typomorphology and the contributions of this knowledge to the architectural design process and the education of students.
Keywords: Architectural context; Architectural design education; Typomorphology; Architectural and urban design; URBAN MORPHOLOGY; FORM; Architecture